A comprehensive modeling on thermal damage in tumor hyperthermia therapies using magneto-plasmonic nanocomposite - Farzad Sadeghi; Hamid Reza M. Zarandi; Hossein Abbastabar Ahangar; Mohammad Hassan Mollaei; Mina Torabi; Mohsen Ghasemi; Vishtasb Soleimanian (Scientific Reports)
Abstract Hyperthermia therapy is an effective approach for tumor treatment. However, its efficiency and potential side effects on normal tissue have not been comprehensively studied. To address this, a 2D modeling study was conducted to minimize harm to healthy tissue while maximizing damage to avascular tumor cells under photothermal and magnetic hyperthermia therapies. The hyperthermia properties of Fe3O4/Au magneto-plasmonic core–shell nanocomposites were modeled using light dissipation and thermal fluctuations. Energy conversion was analyzed for key parameters, including the nanocomposite volume fraction in nanofluid, laser intensity, and magnetic field frequency. Temperature rise and heat distribution in liver tissue were simulated using Pennes’ bio-heat equation, while tissue damage was assessed through the Arrhenius damage model and survival function. By quantifying cell destruction in both normal and tumor regions, overall tissue damage was estimated. The results indicate that optimal conditions exist for achieving maximum tumor cell destruction with minimal impact on healthy tissue. Specifically, the most effective parameters were found to be a laser wavelength of 1064 nm, an intensity of 1 W/cm2, and a magnetic field frequency of 300 kHz, with a nanocomposite volume fraction of 0.002.